2022
DOI: 10.1021/acsomega.2c05918
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Prediction of a B160 Cluster Stuffed by Dual-Icosahedron B12

Abstract: Serving as the premise to understand bulk allotropes, boron clusters have been intriguing experimentalists and theoreticians to study their geometries and chemical bonding. Here, we designed a complete core−shell B 160 cluster stuffed by two B 12 cores, which is energetically preferable over the bilayer structure of the same size. The unprecedented peanutlike structure with C i symmetry has superior stability and exhibits superatomic electronic configuration and spherical aromaticity. Our theoretical work not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…15 Interestingly, the growth behavior of the core-shell motif evolves into a multi-B 12 -core structural pattern in a larger size. 16,17 Parallel to core-shell structures, joint experimental and theoretical investigations have revealed that size-selected boron clusters possess attractive quasi-planar structures in a broad size range, which can be even energetically favorable up to size n = 50. [18][19][20][21][22][23] This has been evidenced by the planar C 6v B 36 cluster with a central hexagonal hole, which was synthesized on the Ag(111) substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Interestingly, the growth behavior of the core-shell motif evolves into a multi-B 12 -core structural pattern in a larger size. 16,17 Parallel to core-shell structures, joint experimental and theoretical investigations have revealed that size-selected boron clusters possess attractive quasi-planar structures in a broad size range, which can be even energetically favorable up to size n = 50. [18][19][20][21][22][23] This has been evidenced by the planar C 6v B 36 cluster with a central hexagonal hole, which was synthesized on the Ag(111) substrate.…”
Section: Introductionmentioning
confidence: 99%
“…15 Interestingly, the growth behavior of the core–shell motif evolves into a multi-B 12 -core structural pattern in a larger size. 16,17…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group has demonstrated that the core–shell structure evolves from B 46 with a B 4 -core to a complete B 96 with an icosahedral B 12 -core, , and a B 12 -core half-covered B 58 bridges the gap . In other words, the core–shell structural motif developed from few-atom core to an icosahedral B 12 core, with the outer shell gradually covering the B 12 -core. , It is worth noting that the multi-B 12 core–shell structural pattern maybe the tendency for large-size boron clusters . The remarkable stability of the core–shell structure is a result of its superatomic electronic configuration of the B 12 -core.…”
mentioning
confidence: 99%
“…21,22 It is worth noting that the multi-B 12 core−shell structural pattern maybe the tendency for large-size boron clusters. 23 The remarkable stability of the core−shell structure is a result of its superatomic electronic configuration of the B 12 -core.…”
mentioning
confidence: 99%